The importance of motor physiotherapy in critical patients in the ICU (International Seven Journal of Multidisciplinary, 2023)
In the hospital environment, the assistance provided by health professionals aims to recover the clinical condition of patients, so that they can return to the reality in which they are inserted with quality of life. As a result of technological and scientific developments and multidisciplinary follow-up, the survival of critically ill patients has increased. The objective theme is to scientifically address the research importance of this study, such as motor physiotherapy in adult patients inserted in UTI. This is an integrative review study; thus allowing a synthesis of works to carry out a broad methodological approach regarding the review, starting from the inclusion of experimental and non-experimental studies for a complete understanding of the analyzed phenomenon The research in the databases resulted in 7 articles that supported the discussion. Physiotherapy has been playing an important role in the clinical recovery of individuals, functional benefits. In view of the research carried out, it is concluded that motor physiotherapy in critically ill patients in an intensive care unit can be performed in different ways, with passive methods, active-assisted, assisted, resisted, with cycle ergometer, sitting and walking, however, the techniques only should be used with the hemodynamic stability of the patient.